Amyloid fibril formation kinetics of low-pH denatured bovine PI3K-SH3 monitored by three different NMR techniques - Gardon, Luis; Becker, Nina; Rähse, Nick; Hölbling, Christoph; Apostolidis, Athina; Schulz, Celina M.; Bochinsky, Kevin; Gremer, Lothar; Heise, Henrike; Lakomek, Nils-Alexander (Frontiers in Molecular Biosciences, 2023)
can be fitted by simple mono-exponential conversion kinetics, with lifetimes τ in the 14 to 38 h range. Atomic force microscopy confirms that fibrils substantially grew in length during the aggregation experiment. This argues for fibril elongation as the dominant growth mechanism in fibril mass (followed by the CP-based solid-state NMR signal).We suggest a combined approach employing both solution NMR and solid-state NMR, back-to-back, on two aliquots of the same sample under seeding conditions as an additional approach to follow monomer depletion and growth of fibril mass simultaneously.